2021
DOI: 10.3390/e23040445
|View full text |Cite
|
Sign up to set email alerts
|

Gravitomagnetic Stern–Gerlach Force

Abstract: A heuristic description of the spin-rotation-gravity coupling is presented and the implications of the corresponding gravitomagnetic Stern–Gerlach force are briefly mentioned. It is shown, within the framework of linearized general relativity, that the gravitomagnetic Stern–Gerlach force reduces in the appropriate correspondence limit to the classical Mathisson spin-curvature force.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Mashhoon [75] investigated the Stern-Gerlach force in a gravitomagnetic framework, in connection with spin-gravity coupling, and showed that it reduces to Mathisson's spin-curvature force. The dynamics of spinning particles in spacetime and the analogies with electromagnetism were investigated by Costa et al [76], and the case of the spacetime of a gravitational wave was considered by Bini et al [77].…”
Section: Other Theoretical Developmentsmentioning
confidence: 99%
“…Mashhoon [75] investigated the Stern-Gerlach force in a gravitomagnetic framework, in connection with spin-gravity coupling, and showed that it reduces to Mathisson's spin-curvature force. The dynamics of spinning particles in spacetime and the analogies with electromagnetism were investigated by Costa et al [76], and the case of the spacetime of a gravitational wave was considered by Bini et al [77].…”
Section: Other Theoretical Developmentsmentioning
confidence: 99%
“…after scattering, where ω is the photon frequency and D is the distance from the photon to the body at the moment of their minimal separation. As the gravitomagnetic field depends upon position, there exists a gravitomagnetic Stern-Gerlach force −∇ðΩ s :NÞ on a spinning particle with "intrinsic" spin vector N. This force naturally leads to a differential deflection of the polarized beams [41].…”
Section: B Angular Separation (θ) Of the Right And Left Circularly Po...mentioning
confidence: 99%
“…The GEM approach has been useful for experimental gravitation [17,27,34] and the method has been applied to a variety of situations [35][36][37]. Henceforth, we will denote the gravitoelectric and gravitomagnetic fields by E g and B g to distinguish them from the corresponding electromagnetic fields.…”
Section: Gravitomagnetic Fieldmentioning
confidence: 99%
“…where I is the 2 × 2 unit matrix and σ = (σ x , σ y , σ z ) are the standard Pauli matrices. In cylindrical coordinates (37), we find…”
Section: Appendix A: Fermion In Gravitomagnetic Fieldmentioning
confidence: 99%

Gravitomagnetic Helicity

Bini,
Mashhoon,
Obukhov
2021
Preprint
Self Cite